The short-term effect of atorvastatin on carotid plaque morphology assessed by computer-assisted gray-scale densitometry: a pilot study - Della-Morte, David; Moussa, Issam; Elkind, Mitchell S; Sacco, Ralph L; Rundek, Tatjana (Neurological research (New York), 2011)
Soft, lipid-containing carotid plaques, which appear echolucent on ultrasound imaging, have been associated with increased risk of ischemic stroke. We sought to investigate the effect of short-term treatment with atorvastatin on the change of carotid plaque echodensity. We treated 40 stroke-free and statin-naive subjects with 80 mg atorvastatin daily for 30 days. Computer assisted gray-scale densitometry (GSD) index was calculated at baseline and 30 days after treatment from the normalized plaque images. A multiple logistic regression was used to assess the effect modification of low-density lipoprotein (LDL) cholesterol on plaque stabilization after adjusting for age, sex, and smoking. The average number of carotid plaques at baseline was 2 (range: 0-5; 27 subjects with carotid plaque) and did not change 30 days following atorvastatin treatment. The mean GSD index significantly increased from 73±16 (range: 1-125) at baseline to 89±15 (range: 1-137) at 30 days after treatment (P<0.05). The adjusted odds ratio for the positive GSD plaque index change (vs. no change or decreased gray-scale median (GSM) index) was 1.71 (95% confidence interval: 1.1-7.6, P<0.01). In conclusion, we observed decreased echolucency (increased echodensity) of carotid artery plaques after short-term treatment with atorvastatin.